UR_GERICHTE 2020_S 19 5 vom 31. Dezember 2020 , 2020_S 19 5. Strafgesetzbuch. Art. 47 Abs. 3 StGB. Jugendstrafgesetz. Art. 3 Abs. 2 JStG. - UR Obergericht (2020)
Strafgesetzbuch. Art. 47 Abs. 3 StGB. Jugendstrafgesetz. Art. 3 Abs. 2 JStG.